SYSTEMS AND METHODS FOR IMPLEMENTING OPERATIONAL TRANSFORMATIONS FOR RESTRICTED COMPUTATIONS OF A MIXED-SIGNAL INTEGRATED CIRCUIT (2021)
Systems and methods for improving a computational performance of a mixed-signal integrated circuit includes identifying a suboptimal graph component of a computation graph of a subject application, wherein: (i) the computation graph comprises a plurality of graphical nodes representing computational operations and a plurality of graphical edges representing data dependencies between the graphical nodes, and (ii) the suboptimal graph component comprises a subset of the plurality of graphical nodes and the plurality of graphical edges that do not satisfy an optimal operation threshold; at compile time, selectively applying an optimizing transformation to the suboptimal graph component based on attributes of a first activation function within the suboptimal graph component, wherein the optimization transformation, when applied, transforms the suboptimal graph component to an optimal graph component that satisfies the optimal operation threshold; and reconstructing the computation graph using the optimal graph component in a place of the suboptimal graph component.